A photonumeric scale for the assessment of atrophic facial photodamage. (16th May 2018) - Ayer, J.; Ahmed, A.; Duncan‐Parry, E.; Beck, P.; Griffiths, T.W.; Watson, R.E.B.; Griffiths, C.E.M.
Summary: Skin ageing occurs naturally over time. This process can be sped up by factors such as sunlight, otherwise known as photodamage. In fair‐skinned individuals, something called hypertrophic facial photodamage (HP) has been reported, with thick, coarse wrinkling, which looks leathery and feels rough, often with irregular colouring. However, another subgroup of facial photodamage has now been described in which individuals have thin, shiny, glossy, skin with broken blood vessels, minimal wrinkling and an increased chance of developing certain skin cancers. This is termed atrophic photodamage (AP). The purpose of this study, conducted in Manchester in the UK, was to develop a scale to assess and measure severity of AP. This had already been done for HP but there was no such scale for measuring AP. This was done by creating a bank of 393 photographs of people with AP and selecting five representative images of different severities to make up the scale. Each image was assigned a number 0 through 8, where 0 was no photodamage and 8 was severe AP, making a nine‐point scale. The photonumeric scale was tested against a scale where the features of atrophic photodamage were described, rather than shown on pictures (descriptive scale). The study clearly demonstrated that the photonumeric scale was significantly better than the descriptive one in terms of repeatability (i.e. producing the same result with different testers) and reproducibility (producing the same result with the same tester a week later). This scale will be a valuable tool to assess and grade AP for clinical studies, particularly as this group seem to have a higher chance of developing certain types of skin cancer. Abstract : Linked Article: Ayer et al. Br J Dermatol 2018;178 :1190–1195